Influence of common and rare genetic variation on warfarin dose among African–Americans and European–Americans using the exome array. (July 2017) - Liu, Nianjun; Irvin, Marguerite R; Zhi, Degui; Patki, Amit; Beasley, T Mark; Nickerson, Deborah A; Hill, Charles E; Chen, Jinbo; Kimmel, Stephen E; Limdi, Nita A
Aim: We conducted a genome-wide association study using the Illumina Exome Array to identify coding SNPs that may explain additional warfarin dose variability.Patients & methods: Analysis was performed after adjustment for clinical variables and genetic factors known to influence warfarin dose among 1680 warfarin users (838 European–Americans and 842 African–Americans). Replication was performed in an independent sample.Results: We confirmed the influence of known genetic variants on warfarin dose variability. Our study is the first to show the association between rs12772169 and warfarin dose in African–Americans. In addition, genes COX15 and FGF5 showed significant association in European–Americans.Conclusion: We identified some novel genes/SNPs that underpin warfarin dose response. Further replication is needed to confirm our findings.